Relationships among two repeated activity tests and aerobic fitness of volleyball players - Meckel, Y.; May-Rom, M.; Ekshtien, A.; Eisenstein, T.; Nemet, D.; Eliakim, A. (The Journal of Strength and Conditioning Research, 2015)
The purpose of the study was to determine performance indices of a repeated sprint test (RST) and to examine their relationships with performance indices of a repeated jump test (RJT) and with aerobic fitness among trained volleyball players. Sixteen male volleyball players performed RST (6 × 30 m sprints), RJT (6 sets of 6 consecutive jumps), and an aerobic power test (20-m Shuttle Run Test). Performance indices for the RST and the RJT were (a) the ideal 30-m run time (IS), the total run time (TS) of the 6 sprints, and the performance decrement (PD) during the test and (b) the ideal jump height (IJ), the total jump height (TJ) of all the jumps, and the PD during the test, respectively. No significant correlations were found between performance indices of the RST and RJT. Significant correlations were found between PD, IS, and TS in the RST protocol and predicted peak VO2 (r = -0.60, -0.75, -0.77, respectively). No significant correlations were found between performance indices of the RJT (IJ, TJ, and PD) and peak VO2. The findings suggest that a selection of repeated activity test protocols should acknowledge the specific technique used in the sport, and that a distinct RJT, rather than the classic RST, is more appropriate for assessing the anaerobic capabilities of volleyball players. The findings also suggest that aerobic fitness plays only a minor role in performance maintenance throughout characteristic repeated jumping activity of a volleyball game.